2013
DOI: 10.1136/bmj.f2450
|View full text |Cite
|
Sign up to set email alerts
|

Use of serum C reactive protein and procalcitonin concentrations in addition to symptoms and signs to predict pneumonia in patients presenting to primary care with acute cough: diagnostic study

Abstract: Objectives To quantify the diagnostic accuracy of selected inflammatory markers in addition to symptoms and signs for predicting pneumonia and to derive a diagnostic tool.Design Diagnostic study performed between 2007 and 2010. Participants had their history taken, underwent physical examination and measurement of C reactive protein (CRP) and procalcitonin in venous blood on the day they first consulted, and underwent chest radiography within seven days. Setting Primary care centres in 12 European countries.Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
219
6
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(245 citation statements)
references
References 46 publications
10
219
6
10
Order By: Relevance
“…Symptom severity 37 (14) 42 (16) 41 (14) 39 (16) 20 (10) 37 (14) 35 (15) 41 (11) 31 (13) 36 (16) 41 (15) 40 (15) 37 ( of patients self-medicated with inhaled corticosteroids (10.8%, of whom none had known COPD or asthma) when compared to other countries and the overall study population (2.9%, of whom 30.1% had known COPD or asthma). Self-medication with salicylic acid was more common in Poland.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptom severity 37 (14) 42 (16) 41 (14) 39 (16) 20 (10) 37 (14) 35 (15) 41 (11) 31 (13) 36 (16) 41 (15) 40 (15) 37 ( of patients self-medicated with inhaled corticosteroids (10.8%, of whom none had known COPD or asthma) when compared to other countries and the overall study population (2.9%, of whom 30.1% had known COPD or asthma). Self-medication with salicylic acid was more common in Poland.…”
Section: Resultsmentioning
confidence: 99%
“…The design and study population of the observational and trial part of the study have been described previously. 14,15 Participating …”
Section: Methods Design and Study Populationmentioning
confidence: 99%
“…Results of our study match with these findings (Graph 1). In another study conducted by van Vugt et al 18 showed the measurement of PCT added no relevant additional diagnostic information. A simplified diagnostic score based on symptoms signs, and CRP >30 mg/mL resulted in proportions of the pneumonia of 0.7, 3.8, and 18.2% in the low, intermediate, and high-risk group respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A number of biomarkers have been considered useful adjuncts for the determination of bacterial pneumonia diagnosis, severity and treatment response in some, but not all, studies. 7,17,26,[39][40][41] Further investigations are certainly needed to confirm the utility of these tests in the patient with CAP who is evaluated as an outpatient. Similarly, the role of rapid diagnostic tests for specific respiratory pathogens in the outpatient setting is still being defined.…”
Section: Discussionmentioning
confidence: 99%